Effect of Material Constituents on Bond Characteristics of Self Consolidating Concrete - Alhamad, Amjad Ahmad (2023)
A Master of Science thesis in Civil Engineering by Amjad Ahmad Alhamad entitled, “Effect of Material Constituents on Bond Characteristics of Self Consolidating Concrete”, submitted in April 2023. Thesis advisor is Dr. Sherif Yehia and thesis co-advisor is Dr. Mohamed Elchalakani. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).